Globo Repórter: Um encontro entre cineastas e a televisão - Ana Claudia de Freitas Resende (2005)
The purpose of this research is to identify the specific characteristics of the documentary and its narrative on the Brazilian television in the 70s and 80s when the sound and image recording changed from pellicle to video. For that purpose, this research takes as a reference the Brazilian programme Globo Repórter, the only programme of the country that was initiated in pellicle, adopted new technologies and is still on the air until today. The sources of this research include literature on the subject and interviews with film directors of cinema and TV, as well as 173 episodes of the programme Globo Repórter, obtained from TV Bahia, in Salvador-BA, and Rede Globo Minas, in Belo Horizonte-MG. This study proposes the existence of a differentiated language adopted by film-makers and reporters in the programmes first two decades, when film-makers were being gradually replaced by the new professionals: the reporters. This research shows that such procedure is formed in the consolidation of the tele-visual language and the transformation of elements that constitute the documentary genesis, such as a new textual form and a different duration of the plans and interviews.